(Re)fractional narrative inquiry: A methodological adaptation for exploring stories. Issue 1 (March 2022) - Guthrie, Kate
Narrative inquiry is relational inquiry in which inquirers come alongside the living, telling, re-living, and re-telling of stories . In this article, I present how I adapted narrative inquiry to explore parent perspectives of their gifted adolescent daughters' experiences of belonging. At the time, I was conducting this study as part of my doctoral dissertation work and as a novice researcher, I struggled with (1) gaining access by a school district to interview adolescent students, (2) believing I could relationally come alongside adolescents as an outsider, and (3) questioning their developmental ability to think reflectively about their stories of belonging. Ultimately, I had to rethink my narrative inquiry approach. Here in this article, I share how I re-conceptualized my methodological approach as (re)fractional narrative inquiry to better understand gifted girls' experiences from the perspectives of those who have relationally lived alongside them. I also present the context and methods of the study, provide a sample of co-negotiated narratives, discuss justifications of my inquiry, and conclude with reflections and evaluations of my adaptations.